Using Cache Optimization Method to Reduce Network Traffic in Communication Systems Based on Cloud Computing - Lanlan Kang; Ruey-Shun Chen; Yeh-Cheng Chen; Chung-Chei Wang; Xingguan Li; Tsu-Yang Wu (IEEE Access, 2019)
The overwhelming increase of population will lead to an increase network traffic usage. In most products, local cache mechanism is implemented for the purpose of reducing the network traffics. However, Due to storage space limitations, lot of times, cache will get purged when there are lots of queries sent and replaced by other newest queries. It is not an efficient by using traditional methodology to build or forming cache. In order to reduce the network traffic usage, the paper propose a solution, which utilizes data mining technique with clustering concept, by gathering the current feedback data that have from our SPN (Smart Protection Network). we are able to form these data in groups with similarity, and by deploying these data to client side, to achieve the reduction of traffic usage. In prototype, this design can really reduce network traffic more than 8%.